Optimalisasi Potensi SDM Gereja Menuju Keberlanjutan melalui Pelatihan Terstruktur, Manajemen SDM Strategis, dan Digitalisasi Layanan - Marumpe, Dody Pratama; Rinaldi, Muhammad; Raihantama, Octa; Putra, Mahesa Ekha; Henbuluh, Genos Moretto; Pangestu, Victor Kurniawan (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The Student Field Work–Community Service (KKM–PKM) program at GKKB Mempawah Church aims to improve the church's service capacity through training, congregation management, and service digitalization. The problems faced include a lack of worship service regeneration, the absence of an integrated data system, and low utilization of digital media. To address these issues, the team designed three programs: From Congregation to Minister (vocal, music, and leadership training), GKKB Mempawah Organized (digital congregation database), and GKKB Connected (social media and landing page). The results include the formation of a new ministry team, a well-organized database, and improved digital connectivity as a model for university-church collaboration.